2003
DOI: 10.2989/16085910309503777
|View full text |Cite
|
Sign up to set email alerts
|

Land use and cover changes in the Likangala catchment of the Lake Chilwa basin, Malawi: implications for managing a tropical wetland

Abstract: This study analyses land use and cover changes in the Likangala River catchment of Lake Chilwa, Malawi, an endorheic tropical African lake. It also examines how land use-related physico-chemical and hydrological parameters in two affluent rivers of the lake affect the migratory and reproductive behaviour of Barbus paludinosus and B. trimaculatus, which are migratory, ecologically and economically important fish species. Land use analysis indicated increasing deforestation and conversion of agricultural land to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 7 publications
(3 reference statements)
3
25
0
Order By: Relevance
“…Results also showed that degraded rivers with reduced river discharge on the Malawi side were devoid of Labeo mesops, while the Mnembo River, which has significantly higher river discharge and a relatively undisturbed catchment, has higher fish biodiversity, including Labeo mesops. Recent studies (Jamu et al, 2003;Delaney et al, 2006;Macuiane et al, 2009) support results of earlier work (Furse et al, 1979b;Kalk et al, 1979) which showed that marshes serve a critical function as breeding and nursery areas and swamps as de facto closed areas or sanctuaries. However, burning of marshes, siltation and conversion of these marshes to rice fields threaten the sustainability of the fishery.…”
Section: The Fisherysupporting
confidence: 67%
See 1 more Smart Citation
“…Results also showed that degraded rivers with reduced river discharge on the Malawi side were devoid of Labeo mesops, while the Mnembo River, which has significantly higher river discharge and a relatively undisturbed catchment, has higher fish biodiversity, including Labeo mesops. Recent studies (Jamu et al, 2003;Delaney et al, 2006;Macuiane et al, 2009) support results of earlier work (Furse et al, 1979b;Kalk et al, 1979) which showed that marshes serve a critical function as breeding and nursery areas and swamps as de facto closed areas or sanctuaries. However, burning of marshes, siltation and conversion of these marshes to rice fields threaten the sustainability of the fishery.…”
Section: The Fisherysupporting
confidence: 67%
“…Although it appears to be resilient to heavy fishing pressure, environmental degradation may pose a greater threat to sustainability of the fishery and hence livelihoods dependent on the lake. For example, Jamu et al (2003) and Delaney et al (2006) showed that high river sediment yield and low river flow had negative impacts on recruitment and spawning migration of Barbus to influent rivers. Results also showed that degraded rivers with reduced river discharge on the Malawi side were devoid of Labeo mesops, while the Mnembo River, which has significantly higher river discharge and a relatively undisturbed catchment, has higher fish biodiversity, including Labeo mesops.…”
Section: The Fisherymentioning
confidence: 97%
“…B 369: 20130052 Lake Chilwa supports the livelihood of over 1.5 million people in the basin through agriculture and natural resource goods and services. Low water levels have negative implications on people's livelihoods through loss of income and employment, reduced fish supply, increased conflicts from competition for resources and increased exploitation of birds [46,48]. Receding water exposes land to crop farming and livestock grazing which negatively impacts wetland vegetation and associated biodiversity [48].…”
Section: Ecosystem and Livelihood Benefits Of Selected Small African mentioning
confidence: 99%
“…Low water levels have negative implications on people's livelihoods through loss of income and employment, reduced fish supply, increased conflicts from competition for resources and increased exploitation of birds [46,48]. Receding water exposes land to crop farming and livestock grazing which negatively impacts wetland vegetation and associated biodiversity [48]. Crowding of fishing villages which remain with adequate water levels for fishing has also resulted in poor sanitation [49].…”
Section: Ecosystem and Livelihood Benefits Of Selected Small African mentioning
confidence: 99%
See 1 more Smart Citation